Modelos pedagógicos en primero de básica de la escuela “Carlos Aguilar”. - Cárdenas Chinchero, Paola Lizeth (2018)
This research work was carried out with children of basic first of the school Carlos Aguilar, located in the city of Quito, Parish of Cumbayá. The research work was carried out, with the purpose of knowing what is the pedagogical model with which it is worked in this institution and being able to analyze it with the institutional Education Project (PEI), the annual curriculum Plan (PCA) and the planning of the same one, It also relates to the model used in the school with the 2016 basic general education curriculum. To be able to collect the data the institution was visited. Three instruments were applied to be able to know the pedagogical model they use, one of them was the interview questionnaire to the principal and the teacher, the second was an observation guide where ten observation variables were established, and finally, field diaries were used. At the end of the investigation it can be considered that the children of first basic of the school Carlos Aguilar, work with two pedagogical models one of them is the model constructivist partner and the second model is the Cognitivist, the same ones that allow to the Child and girl build their own knowledge from what each has as an experience or teaching. In addition, the role of the teacher is a mediator, as it gives guidelines for the student to continue enriching their teaching-learning.